The GLIM Criteria Represent a More Appropriate Tool for Nutritional Assessment in Patients With Crohn's Disease - Li, Yong; Peng, Ziheng; Xu, Duo; Peng, Yu; Liu, Xiaowei (Frontiers in Nutrition, 2022)
Background The early recognition of malnutrition is essential for improving the prognosis of patients with Crohn’s disease (CD). The Global Leadership Initiative on Malnutrition (GLIM) criteria represent a new consensus for the diagnosis of malnutrition but need to be validated in CD. The aims were to explore the related factors of malnutrition in CD and explore whether GLIM-positive patients who did not meet the Nutritional Risk Screening 2002 (NRS 2002) would benefit from nutritional treatment. Methods This study retrospectively enrolled patients with CD at the Gastroenterology Department of Xiangya Hospital Central South University between March 2020 and March 2021. After bioelectrical impedance analysis, all patients underwent nutritional screening and diagnosis using the NRS 2002 and GLIM criteria, respectively. Multivariable analysis was performed to evaluate risk factors related to malnutrition in patients with CD. A multivariable Cox hazard model was used to assess the association between nutritional therapy and prognostic outcomes. Results Of the 118 patients included, fifty were classified as having a high malnutrition risk according to the NRS 2002, while 76 were diagnosed with malnutrition by the GLIM criteria. Multivariate analysis showed that a high malnutrition risk was independently associated with the L4 phenotype (odds ratio (OR) (95% confidence interval (CI)) =4.718 (1.108, 20.10), p=0.036) and Crohn's Disease Activity Index (CDAI) (OR (95% CI) =1.018 (1.007, 1.029), p=0.002) based on the NRS 2002. The age at onset (OR (95% CI) =0.828 (0.699, 0.980), p=0.028) and CDAI (OR (95% CI) =1.111 (1.034, 1.195), p=0.004) were regarded as independent risk factors related to malnutrition, as determined by the GLIM criteria. Among 26 GLIM+/NRS- patients, significantly more patients who received nutritional support achieved 6-week remission than patients who did not (100% vs. 71.4%, p< 0.05). The 6-week remission risk in patients treated with nutrition therapy was more than four-fold higher than those without nutritional therapy. Conclusion The GLIM criteria could diagnose more malnourished patients with CD who are not positively screened by the NRS 2002, among whom nutritional support therapy would be beneficial for disease remission. The new criteria should be more appropriate for assessing the nutritional status of patients with CD.